The Effect of Exposure to Social Media Instagram @Narasinewsroom Regarding Online Fraud on Students' Vigilant Attitude - Mutia Khairunnisa; KYS Putri; Dini Safitri (Universitas Lambung Mangkurat, 2024)
Online fraud continues to haunt internet users, especially WhatsApp as a messenger media which is the main medium for communication. The motive is now to spread messages such as couriers, wedding invitations, or bill payments by sending .apk format to break into the victim's account. This became a concern and was reported by Instagram @narasinewsroom. Uploaded news can form a wary attitude among readers. The aim of this research is to determine the influence of exposure to the social media Instagram @narasinewsroom regarding online fraud on students' alert attitudes. The paradigm used is positivism with a quantitative approach. The sample used consisted of 100 Communication Science students at Jakarta State University and used a simple random sampling technique. The results of this research show that there is an influence between exposure to social media Instagram @narasinewsroom regarding online fraud on students' alert attitudes with a weak correlation, namely 13%.